Regulasi Regenerasi Petani dalam Konteks Ketahanan Pangan: Sebuah Upaya dan Jaminan Perlindungan Hak Atas Pangan - Moch. Marsa Taufiqurrohman; Dilla Restu Jayanti (Jurnal HAM, 2022)
There is so much recognition that the availability of land, technology, seeds and weather only determines food security. However, evidence suggests that farmer availability has an important role in overcoming food security challenges. Indirectly, guaranteeing the availability of farmers is an important indicator to ensure the right to food. This article aims to discuss how farmer availability and regeneration are related to food security. This article also wants to reflect on how the availability of adequate policies on agricultural sustainability has an important meaning in guaranteeing the right to food. By using normative legal research and Reform Oriented Research, this article will answer several problems. First, how is the relation between farmer regeneration and food security? Second, what is the state's responsibility to guarantee the right to food? Third, how is the formula of farmer regeneration policies to maintain food security? This article clarifies that farmer availability has a significant influence on food production. This article also finds that the state has an important role in developing agricultural regulations to guarantee food security. At its peak, this article proposes targeted policy support to enable the availability of regulations on farmer regeneration to address food security challenges.